On the Observability of Leader-Based Multiagent Systems with Fixed Topology - Bo Liu; Ningsheng Xu; Housheng Su; Licheng Wu; Jiahui Bai (Complexity)
This paper investigates the observability of first-order, second-order, and high-order leader-based multiagent systems (MASs) with fixed topology, respectively. Some new algebraic and graphical characterizations of the observability for the first-order MASs are established based on agreement protocols. Moreover, under the same leader-following framework with the predefined topology and leader assignment, the observability conditions for systems of double-integrator and high-integrator agents are also obtained. Finally, the effectiveness of the theoretical results is verified by numerical examples and simulations.